Immersive virtual reality, augmented reality and mixed reality for self-regulated learning: a review - Pedrosa, Daniela (2023)
Immersive technologies, such as virtual reality, augmented reality, and mixed reality have gained increasing interest and usage in the field of education. Attention is being paid to their effects on teaching and learning processes, one of which is self-regulation of learning, with an important role in supporting learning success. However, designing and creating immersive environments that support the development of SRL strategies is challenging. Employing a systematic approach, this literature review provides an overview of the uses of virtual, augmented, and mixed reality with the goal of supporting SRL. We map these to known educational uses of immersive environments, highlighting current gaps in these efforts and suggesting pathways for future studies on instructional design of the use of immersive technologies to support self-regulation of learning.